2011
DOI: 10.1590/s1678-58782011000300009
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Soft Tooling Process Through Particle Reinforcement with Polyurethane Mould

Abstract: Use of conventional flexible polymeric mould materials yields to longer solidification time of (wax/plastic)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…A significant amount of research work was found in the literature where particulate conductive fillers were incorporated into polymer to increase its effective thermal conductivity [1][2][3][4][5][6][7][8][9][10]. Through experimental study, it has been observed that the solidification time in soft tooling process is significantly reduced by reinforcement of conductive filler into flexible polymeric mould material [11,12]. However, reinforcement of filler material into the polymer not only increases the equivalent thermal conductivity but also affects physical and mechanical properties such as equivalent hardness of composite mould material.…”
Section: Introductionmentioning
confidence: 99%
“…A significant amount of research work was found in the literature where particulate conductive fillers were incorporated into polymer to increase its effective thermal conductivity [1][2][3][4][5][6][7][8][9][10]. Through experimental study, it has been observed that the solidification time in soft tooling process is significantly reduced by reinforcement of conductive filler into flexible polymeric mould material [11,12]. However, reinforcement of filler material into the polymer not only increases the equivalent thermal conductivity but also affects physical and mechanical properties such as equivalent hardness of composite mould material.…”
Section: Introductionmentioning
confidence: 99%